2015
DOI: 10.1186/s12967-015-0415-2
|View full text |Cite
|
Sign up to set email alerts
|

A chimeric EBV gp350/220-based VLP replicates the virion B-cell attachment mechanism and elicits long-lasting neutralizing antibodies in mice

Abstract: Epstein-Barr virus (EBV), an oncogenic gammaherpesvirus, causes acute infectious mononucleosis (AIM) and is linked to the development of several human malignancies. There is an urgent need for a vaccine that is safe, prevents infection and/or limits disease. Unique among human herpesviruses, glycoprotein (gp)350/220, which initiates EBV attachment to susceptible host cells, is the major ligand on the EBV envelope and is highly conserved. Interaction between gp350/220 and complement receptor type 2 (CR2)/CD21 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 54 publications
4
70
0
Order By: Relevance
“…It has been reported that gp350 DNA vaccine induced effective immune responses against the antigen, and the major isotype of the gp350-specific antibodies was IgG1 (Jung et al 2001). The chimeric gp350 virus-like particles also induced a dominant IgG1 subclass response (Ogembo et al 2015). In the present study, the recombinant gp350 1-443 induced significant IgG1 and IgG2a antibody responses, demonstrating that gp350 1-443 elicited a systemic Th1/Th2 immune response.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It has been reported that gp350 DNA vaccine induced effective immune responses against the antigen, and the major isotype of the gp350-specific antibodies was IgG1 (Jung et al 2001). The chimeric gp350 virus-like particles also induced a dominant IgG1 subclass response (Ogembo et al 2015). In the present study, the recombinant gp350 1-443 induced significant IgG1 and IgG2a antibody responses, demonstrating that gp350 1-443 elicited a systemic Th1/Th2 immune response.…”
Section: Discussionsupporting
confidence: 62%
“…Options for developing safe prophylactic EBV vaccines have been limited due to the oncogenic potential of EBV (Ogembo et al 2015). As the most abundant glycoprotein on the surface of EBV and virus-infected cells, gp350 is an attractive candidate for development of a prophylactic subunit vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, there is no available vaccine to protect against EBV infection. One possible approach to developing such a vaccine would be to target gp350 or other viral proteins [73]. A small trial evaluating a vaccine against EBV showed limited results in MS [74].…”
Section: Vaccinationmentioning
confidence: 99%
“…Flow cytometric analysis was performed on an LSRII benchtop FC (Becton-Dickinson, B-D) and data was analyzed using CellQuest Pro Version 4.0.1 (BD Biosciences) and/or FlowJo Cytometry Analysis software (FlowJo, LLC) as described [20]. All the experiments were independently repeated at least three times unless otherwise specified.…”
Section: Methodsmentioning
confidence: 99%